The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-09848-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin-6 levels associated with malaria infection and disease severity: a systematic review and meta-analysis

Abstract: Interleukin-6 (IL-6) is generated by immune cells during infection with malaria parasites and they are associated with the immunopathogenesis of malaria. The present systematic review and meta-analysis aimed to compare the differences in IL-6 levels between several groups of patients with malaria and healthy control groups. The systematic review was registered at PROSPERO with a registration number: CRD42021290753. Systematic literature searches were conducted in PubMed, Web of Science, and Scopus until Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…A recent meta-analysis confirmed that IL-6 is prognostic for severe outcomes, and differentiates uncomplicated from severe malaria. 2 However, our work suggests, in contrast to COVID-19 (and perhaps bacterial sepsis), those with genetically proxied reduced IL-6 signalling do not have altered risk of severe disease. 7,8 IL-6 levels are raised (and associate with) a huge number of conditions, and so it is plausible that IL-6 may represent a useful biomarker but one that is not causally related to severe malaria.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A recent meta-analysis confirmed that IL-6 is prognostic for severe outcomes, and differentiates uncomplicated from severe malaria. 2 However, our work suggests, in contrast to COVID-19 (and perhaps bacterial sepsis), those with genetically proxied reduced IL-6 signalling do not have altered risk of severe disease. 7,8 IL-6 levels are raised (and associate with) a huge number of conditions, and so it is plausible that IL-6 may represent a useful biomarker but one that is not causally related to severe malaria.…”
Section: Discussionmentioning
confidence: 58%
“…1 Increased IL-6 is known to be associated with mortality within severe malaria, and studies have suggested that it may be causal for worse outcomes. 2,3 However, animal models have so far failed to identify robust evidence that IL-6 manipulation (e.g. therapeutic blockade) improves outcomes in severe malaria, although data are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Egger’s test with statistical significance ( p < 0.05) might indicate that funnel plot asymmetry was due to a small-study effect [ 26 ]. A contour-enhanced funnel plot was used to explore the cause (s) of funnel plot symmetry [ 27 ]. To investigate potential sources of variation, research designs, study sites, Plasmodium spp., age groups and methodologies for IL-1β measurement were used as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…We used the JBI tools for case-control and cohort studies to determine the quality of those study designs. The quality of the included studies was rated using the percentile as described previously [16,17].…”
Section: Quality Assessmentmentioning
confidence: 99%